VALIDATION AND IMPLEMENTATION OF FAILURE PARAMETERS IN INTEGRATED SIMULATIONS FOR SHORT FIBRE REINFORCED POLYPROPYLENE - Anna Kalteis; Martin Reiter; Michael Jerabek; Zoltán Major (Acta Polytechnica CTU Proceedings)
Nowadays short fibre reinforced polymers are often used in load carrying structural parts. Compared to continuous fibre reinforced polymers they exhibit a more complex morphology. Hence the determination of the strength is a difficult but important task. Therefore this was the objective of this research. The strength of short fibre reinforced polymers was numerically determined for low-speed to high-speed strain rates for specimens with different fibre orientations. For the failure modelling the micromechanical approach “First pseudo grain failure” in Digimat was used. The parameters for the material and failure description were determined with the reverse engineering method. Integrated finite element simulations were performed to validate the material and failure models by tensile and bending tests with different specimens. The comparison of the results of the experiments and simulations showed low deviation.